Computer-Aided Designing and Manufacturing of Lingual Fixed Orthodontic Appliance Using 2D/3D Registration Software and Rapid Prototyping. (11th May 2014) - Kwon, Soon-Yong; Kim, Yong; Ahn, Hyo-Won; Kim, Ki-Beom; Chung, Kyu-Rhim; Kim (Sunny), Seong-Hun
Abstract : The availability of 3D dental model scanning technology, combined with the ability to register CBCT data with digital models, has enabled the fabrication of orthognathic surgical CAD/CAM designed splints, customized brackets, and indirect bonding systems. In this study, custom lingual orthodontic appliances were virtually designed by merging 3D model images with lateral and posterior-anterior cephalograms. By exporting design information to 3D CAD software, we have produced a stereolithographic prototype and converted it into a cobalt-chrome alloy appliance as a way of combining traditional prosthetic investment and cast techniques. While the bonding procedure of the appliance could be reinforced, CAD technology simplified the fabrication process by eliminating the soldering phase. This report describes CAD/CAM fabrication of the complex anteroposterior lingual bonded retraction appliance for intrusive retraction of the maxillary anterior dentition. Furthermore, the CAD/CAM method eliminates the extra step of determining the lever arm on the lateral cephalograms and subsequent design modifications on the study model.